LEGAL REVIEW OF LATE PAYMENT OF SYNDICATED BANK CREDIT AGREEMENTS DUE TO COVID-19 - Zulyadi, Rizkan; Munawir, Zaini; Pohan, Mahalia Nola (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
Lenders in the form of loans provided by domestic or foreign lenders or banks. The lenders formed a syndication together to fund the borrower's business operations. The choice of law and the choice forum chosen largely determine the legal form for each party. How to arrange syndicated loans in Indonesia involving domestic and foreign bank participants, and the implementation of collateral in the implementation of syndicated loan agreements with banks? This type of research is normative, and prescriptive in law, providing legal arguments for international syndicated loan approvals in the framework of providing legal protection to lenders. The data used are secondary data obtained through literature study and analyzed qualitatively. International syndicated loan arrangements according to law in Indonesia do not apply legal lending limit if a primary bank is provided as a major bank that is included in one of the 200 (two hundred) major global banks determined by the banker's almanac. With the rise of the Covid-19 pendemik case, it has become a problem of delays in credit payments, including declining syndicated loan payments from domestic and foreign banks. The consideration of this paper is the question of syndicated loans in Indonesia involving domestic and foreign banks and also the implementation of legal options, Jurisdiction of Settlement of Syndicated Credit Disputes at Domestic and Foreign Banks, and legal protection against Congestion 19.